What emerging adults say about the appropriateness of sexual and reproductive health programmes: evidence from a suburb in Accra, Ghana - Sowah, Laud R.; Biney, Adriana A. E.; Atiglo, D. Yaw; Badasu, Delali; Boateng, Angela A.; Sarfoh, Kwadwo Ohene; Ankomah, Augustine (Frontiers in Reproductive Health, 2024)
IntroductionYoung people's access to appropriate health information in Ghana has been marginal, hence their utilisation of existing services remains poor. Most sexual and reproductive health (SRH) policies and outreach programmes target adolescents, neglecting emerging adults who are equally vulnerable to SRH risks. This study seeks to elicit emerging adults’ knowledge and experiences with SRH programmes, and their recommendations to improve the services for their needs.MethodsUsing data from 30 in-depth interviews and 10 focus group discussions with youth aged 18–24 years in a suburb of Accra, we provide insights on emerging adults’ experiences with SRH programmes and their recommendations for their improvement, as well as young men's perspectives on SRH programmes, in particular.ResultsThe participants were in three socio-economic groups: tertiary students, informal workers and apprentices. The main SRH education that the emerging adults had received was from their earlier formal education in Junior and Senior High Schools but not in their current places of school or work. However, they indicate that the SRH education programmes and information they received earlier in life were inadequate to tackle pragmatic issues that contemporary youth face. Furthermore, SRH programmes operate in unfriendly environments with negative messages that cause them to lack vital information.DiscussionFor the success of SRH programmes, the youth should be targeted with diverse contemporary approaches specific for their SRH needs. Key recommendations comprised making available SRH education tailored for emerging adults’ current demographic and socio-economic groups, and providing appropriate SRH content and youth-friendly community centres.